THE SYMBOLISM OF HOPE IN THE LYRICS OF A NEW DAY HAS COME AND I’M ALIVE IN CELINE DION’S ALBUM A NEW DAY HAS COME - Rumambi, Trifena M. (Journal of English Language and Literature Teaching, 2023)
The purpose of this study is to identify thesymbols of hope in Celine Dion’s songs A New Day Has Come and I’m Alive in the Album A New Day Has Come. Descriptive qualitative design is used in this research. The data were collected by listing the lyrics per stanza and line of Celine Dion’s two chosen songs that being suitable with the main purpose of this research. The analysis of the data oriented on the objective approach according to M. H. Abrams. The findings show that the symbols of hope were strongly presented in two chosen songs. The presentation of hope was dominated by symbols in the form of figurative language which are metaphor and personification. Those symbols were revealed hope that encouraged listener for never give up hoping and keep motivated to face daily life. Furthermore, it is expected that this study will be useful for the further researchers that about to conduct the study related and helpful for the readers to study poetry in song, especially in essence.